Composição corporal na Síndrome da Quilomicronemia familiar - Ramos, Lorena Taúsz Tavares (2023)
Familial chylomicronemia syndrome (FCS) is a rare condition of autosomal recessive inheritance, characterized by deficiency in the activity of the enzyme lipoprotein lipase (LPL), which represents the majority of cases, or of one of its cofactors (APOC2, APOA5, LMF1 and GPIHBP1), implying the inability to metabolize triglycerides (TG) and resulting in severe hypertriglyceridemia (HTG). Those affected are usually thin, given the usual dietary restriction. However, the body composition of these patients has been little studied so far, especially with more accurate clinical methods. Thus, the present study aimed to evaluate the body composition of individuals with FCS. This is a cross-sectional, descriptive study with an analytical component conducted between November 2020 and January 2023 at the dyslipidemia outpatient clinic of the Endocrinology and Diabetes Service of the Hospital Complex of the Federal University of Ceará/Ebserh. All patients with FCS-related pathogenic variants older than 18 years were included. Socioeconomic data, body composition, clinical parameters, and laboratory tests were collected. Continuous variables were described as median (minimum-maximum) and categorical variables as relative and absolute frequency. Spearman's correlation test was used to correlate the variables. A significance level of 5% was adopted. Nine patients were evaluated, of which seven had a pathogenic variant in LPL (FCS-LPL) and the others in the APOA5 and GPIHBP1 genes (FCS-non-LPL). All patients had serum TG levels > 500 mg/dL during follow-up. FCS-LPL had the most severe clinical presentation, earlier detection of HTG, recurrent symptoms, maintenance of higher TG levels, and higher occurrence of acute pancreatitis (AP). FCS-LPL had normal values for body mass index (BMI), waist circumference (WC) and body fat percentage (%BF), while those FCS-non-LPL had overweight/obesity and increased WC and %BF. In dual-emission X-ray absorptiometry (DEXA), high values were also observed for visceral adipose tissue (VAT), android fat % and android/gynoid fat ratio >1.0 in those FCS-non-LPL. FCS-non-LPL individuals seem to have a different phenotype from those with pathogenic variants in the LPL gene, both in quantity and distribution of body adiposity. This is the first study demonstrating such findings of body composition differences in different etiologies of FCS.